Pengembangan Potensi TOGA di Desa Pucang Anom sebagai Wirausaha Minuman Herbal Celup dan Jelly Milkshake - Yoaga L. Permana; Dana F. Nuriyanto; Fikriatul A. Ramadani; Adhi W. Mahardhika; Ilona Asteria; Dies R. Setyoningsih; Gias P. Putra; Muhammad Rofiq; Kevin Y. Marpaung; Denna E. Munandar; Sundahri (Jurnal Pengabdian Magister Pendidikan IPA, 2023)
Pucang Anom is one of the villages in Bondowoso which is known to have potential in agriculture. This can be proven by the breadth of land in Pucang Anom village, which almost 60% of the total is dominated by agricultural lands. This village has an abudant potential of famili medicinal plants (TOGA), but still underutilized and underestimated by the community. Even though TOGA can be processed into a product that has a high sale valus addition to the great benefits at the time of of the corona virus outbreak that is spreading through out the world. Therefore, KKN 04 Pucang Anom University of Jember on 6th of January until 19th of February 2020 had explored the potential in the village through the entepreneurship development of TOGA as herbal beverage that rich in benefits. TOGA as a variety of its preparations that could be consumed by people invarious circles. The target of the program was to raise the enthusiasm of the community for enterpreneurship that was focused on processing technology and manufacturing products that did not yet exist in Pucang Anom village. Based on public response, it was known that 57% stated that they “really like” herbaldyed products and prossesed Herbal Jelly Milkshake, 100% said they werw “attracted” to the products, 95% said the were “innovative” products, and 100% stated thet the continuation of business potential was “needs to be continued”. Finally, the products won 1st place in the Product Expo of KKN Students of the University of Jember at 1st period in 2019/2020 academic year which was held on February 26, 2020.